Faktor-Faktor yang Mempengaruhi Minat Nasabah Memilih Asuransi Syariah - Muksal, Muksal; Ayumiati, Ayumiati; Yuliadra, Teuku Fariz (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
The purpose of this research is to examine the joint and many effects of the company's image, premium rates, and promotions on consumers' propensity to select PT. Banda Aceh Family Takaful. A total of 68 participants were selected at random for this quantitative investigation. The findings of the simultaneous and partials tests indicate that PT. Family Takaful Banda Aceh Branch's corporate image, premium rates, and promotions all have a favorable and statistically significant effect on customers' propensity to purchase insurance from the company. The R-Square value for this study is 56.1%, indicating its significance, with the remaining 43.9% attributable to confounding variables.